Taller para la introducción de la música regional del departamento de Córdoba en la Institución Educativa Marco Fidel Suarez del municipio de Ciénega de Oro, tomando como referencia la obra musical de Pablo Flores Camargo (2022)
This formative research that is presented in the following document, and that was developed in the MARCO FIDEL SUAREZ EDUCATIONAL INSTITUTION of the Municipality of Ciénaga de Oro, in Grades 3, 4, 5, of Basic Primary. Called "Workshop for the introduction of regional music of the department of Córdoba in the Marco Fidel Suárez educational institution of the municipality of Ciénaga de Oro, taking as a reference the musical work of Pablo Flórez Camargo", it is framed within the qualitative paradigm, with a of research-action in which there is an interpretive and naturalistic approach to the subject of study, since it analyzes the musical artistic qualities of the student. This type of qualitative research is based on education as a field of knowledge and creativity, where, in addition, the research group seeks to strengthen and disseminate our intangible heritages